QUIZIZZ E-ASESMEN FORMATIF: PENGEMBANGAN DALAM PENILAIAN SISTEM REPRODUKSI TINGKAT SMA - Amaliya Fajri; Nur Fadhilla, Devi; Amellia Harnum, Inggit; Hendi Ristanto, Rizhal; Isfaeni, Hanum (Jurnal Muara Pendidikan, 2024)
Materials about the reproductive system are often considered difficult by students, but have a significant influence on their awareness of the importance of maintaining healthy reproductive organs and obtaining appropriate sexual education. Assessment is a structured process to collect information about student achievement in learning. One of the assessment methods that can be applied by teachers is formative assessment. The application of formative assessment can be done by utilizing technological advances, such as the use of quizizzes. Therefore, this study aims to develop a quizizz-based formative assessment for reproductive system material in class XI, with the aim of evaluating the feasibility of the product through validity testing, item reliability testing, difficulty level testing, and differentiation testing. The method used was R&D (Research and Development) with Thiagarajan's 4D approach. The research subjects consisted of 20 XI grade students in one of the high schools in Bojongkulur. The results obtained from several product validation tests by validators show that: The logical validity test reached 85.17%, out of 25 items, 20 were declared valid and 5 were invalid. Reliability of formative assessment questions shows a fairly good level of reliability with a reliability coefficient of 0.62. The findings of this study are in line with the core and basic competencies, able to measure students' high level of cognition, and effective in distinguishing between students with high and low abilities.